Do Adult Learners Who Engage in Torah Study as a Leisure Activity Report Higher Levels of Meaning in Life than Learners of General Enrichment Studies? - Alkan, Ora; Davidovitch, Nitza; Kushnir, Talma (Journal of Education Culture and Society, 2023)
Aim. The aim of the research is to assess whether adult learners engaged in Torah/Bible studies report higher levels of psycho-social resources, specifically spirituality, meaning in life, hope, and social support, than learners who attend general enrichment courses, and whether psycho-social resources contribute to their meaning in life. Methods. Participants were 234 men and women over age 55 who study regularly in their leisure time: 56 Torah students in the hevruta (communal learning) method, 50 Torah students who participated in frontal Torah lectures, and 128 adults who attended lectures on various enrichment subjects. Participants completed self-report questionnaires that included demographic information and characteristics of the course, evaluations of the learning experience, the Spiritual Health and Life-Orientation Measure, the Snyder Hope Questionnaire, the Multidimensional Scale of Perceived Social Support (MSPSS), and the PIL – Purpose in Life questionnaire. Results. Torah and enrichment learners did not differ in meaning of life and hope. Torah learners reported a stronger learning experience, higher levels of transcendentality (an aspect of spirituality), and more social support from their peer group. For all learners, social support from the family was the strongest contributor to meaning in life, followed by hope and finally the communality aspect of spirituality. Conclusions. Findings confirm the importance of the human need for relatedness in determining meaning and suggest that the social milieu in which the leisure activity is held may be more important for cultivating meaning in life than the discipline studied.